2018
DOI: 10.3389/fimmu.2018.00594
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Regulatory T Cell Activity by TNF Receptor Type II-Targeting Pharmacological Agents

Abstract: There is now compelling evidence that tumor necrosis factor (TNF)–TNF receptor type II (TNFR2) interaction plays a decisive role in the activation, expansion, and phenotypical stability of suppressive CD4+Foxp3+ regulatory T cells (Tregs). In an effort to translate this basic research finding into a therapeutic benefit, a number of agonistic or antagonistic TNFR2-targeting biological agents with the capacity to activate or inhibit Treg activity have been developed and studied. Recent studies also show that tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 110 publications
2
35
0
Order By: Relevance
“…This wide cellular expression in the immune system makes TNF a crucial regulator of autoimmune responses, which explains the development of a plethora of anti-TNF drugs for autoimmune disorders (see later paragraph 4). Due to the complexity of the immune responses mediated by TNF and for the aim of this review, we provide a brief overview on TNF role in T cell-subset function and we refer the reader to more detailed reviews on this topic [ 37 , 38 ].…”
Section: Pathophysiological Role Of Tnf In the Immune System And Tmentioning
confidence: 99%
See 1 more Smart Citation
“…This wide cellular expression in the immune system makes TNF a crucial regulator of autoimmune responses, which explains the development of a plethora of anti-TNF drugs for autoimmune disorders (see later paragraph 4). Due to the complexity of the immune responses mediated by TNF and for the aim of this review, we provide a brief overview on TNF role in T cell-subset function and we refer the reader to more detailed reviews on this topic [ 37 , 38 ].…”
Section: Pathophysiological Role Of Tnf In the Immune System And Tmentioning
confidence: 99%
“…It has recently become apparent that TNF can exert a strong activity on CD4+ Tregs, which are a subset of CD4+ T cells that help to prevent or treat autoimmunity by maintaining self-tolerance, immune homeostasis, and suppression of cytotoxic T cells [ 50 ]. Mounting evidence indicate a crucial role of TNFR2 in Treg biology, supporting the development of drugs specifically targeting TNFR2 to potentiate or weaken Treg functions in autoimmune disorders [ 38 ]. Indeed, TNFR2 is upregulated in activated Tregs [ 41 ] and can promote itself the proliferation and expansion of Tregs [ 51 , 52 ].…”
Section: Pathophysiological Role Of Tnf In the Immune System And Tmentioning
confidence: 99%
“…The opposite approach that is currently investigated implies TNFR2 activation to stimulate the TNFR2-mediated protective pathways in autoimmunity and neurodegenerative diseases [352]. It has been suggested that this strategy might be superior to TNFR1 antagonism because of the restricted cellular expression of TNFR2.…”
Section: Selective Tnfr2 Targetingmentioning
confidence: 99%
“…[ 11 13 ] Antitumor necrosis factor α (Anti-TNF-α) antibodies interfere with endogenous TNF-α activity via binding to human TNF-α what plays a decisive role in activation, expansion, and phenotypical stability of T cells. [ 10 , 14 , 15 ] Thus, both calcineurin inhibitors and anti-TNF-α antibodies have been considered for UC therapy. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%